When do Board and Management Resources Complement Each Other? A Study of Effects on Corporate Social Responsibility - Galbreath, Jeremy (Springer Netherlands, 2014)
Following resource-based and complementary asset perspectives, this paper examines the effects of board and management resources on corporate social responsibility (CSR) in a sample of large Australian public firms. Specifically, this study posits that outside directors and women on boards are complementary in that their multiplicative effect incrementally influences CSR above their individual, independent effects. The hypothesis is confirmed. Further, the study tests the interactive effect of a senior CSR manager, determining the independent and complementary effects of managerial resources upon board resources. The results suggest that a senior CSR manager has both an independent and complementary effect, offering support for the hypotheses. The findings offer some confirmation of resource-based theory, demonstrating that board resources can be complementary within the boardroom context and complementary to management in positively affecting firm outcomes.